PERBEDAAN INFORMASI ANATOMI PADA SEKUEN T1WI TSE POST GADOLINIUM DENGAN FATSATURASI MAUPUN TANPA FAT SATURASI PADA PEMERIKSAAN MRI LUMBAL - Marichatul Jannah; Sugiyanto; Irwan Katili; Edy Susanto (Perhimpunan Radiografer Indonesia (PARI), 2018)
Backgroud: Fat Saturation is useful in MR Imaging to supress high signal from fatty tissues. When Fat Saturation is used in combination with gadolinium, enhancing lessions become more conspicuous. T1 post-contrast examination usually does not require fat saturation, in Dr. Hasan Sadikin Hospital Bandung combined with fat saturation. Another interesting things are the tumor, metastasis and inflammation will be isointense on T1 enhance contrast but still added Fat Saturation. The objectives of this research is to find out anatomy information differences between TIWI TSE Post Gadolinium with and without Fat Saturation and acknowledge which better anatomy information between two pulse sequences. Methods: The research uses quantitative method with experimental approach and questionnaire. The research takes place at Radiology Unit RSUP Dr. Hasan Sadikin Bandung on May-June 2013 with 20 patients with a variety of cases using gadolinium and 5 respondents. Data analysis uses univariate method, wilcoxon test, and friedman test Results: The research result shows that are differences anatomy information between TIWI TSE Post Gadolinium with and without Fat Saturation by P value 0,000 (sig.<0,05). The anatomy information has good present on the first treatment T1WI TSE Post Gadolinium with Fat Saturation pulse by mean rank 2,99